Clinical characteristics and outcomes of chronic obstructive pulmonary disease patients with family history of chronic airway disease - Cong Liu; Qing Song; Ya-ting Peng; Wei Cheng; Ling Lin; Tao Li; Xue-shan Li; Yu-qin Zeng; Ai-yuan Zhou; Yan Chen; Shan Cai; Ping Chen (Annals of Medicine)
Background Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous condition with different risk factors, including family history. This study aimed to explore association between a family history of chronic airway disease and features and outcomes of COPD.Methods Participants were obtained from the RealDTC study between December 2016 and December 2022. Data on demographics, pulmonary function, history of exacerbation at baseline, acute exacerbation during 1-year follow-up and survival status during 3-years follow-up were collected.Results 5020 patients were enrolled, with 1307 patients (26.0%) having a family history of chronic airway diseases. Compared with patients without a family history of chronic airway diseases, patients with a family history had a lower forced expiratory Volume in one second (FEV1), higher Modified Medical Research Council (mMRC) score and COPD Assessment Test (CAT) score, higher rate of acute exacerbation and hospitalization in the past year (p < 0.05) and rate of acute exacerbation and hospitalization during 1 year follow-up period (p < 0.05). It was an independent risk factor for acute exacerbation (OR = 2.196; 95% CI =1.873–2.576) and hospitalization (OR = 2.199; 95% CI =1.812–2.670). Over 3 years of follow-up, there were no significant differences in mortality rates and annual changes in FEV1 between two groups.Conclusion COPD patients with a family history of chronic airway disease are not rare, and they tend to have more severe symptoms and a higher risk of future deterioration. In the management of COPD, special attention should be paid to patients with a family history of chronic airway disease.